Study on Binding Properties of Poorly Soluble Drug Trimethoprim in Anionic Micellar Solutions - GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2014)
Binding and distribution properties of trimethoprim (TMP) in the presence of various anionic surfactants; sodium octyl sulfate (C8SO4Na), sodium decyl sulfate (C10SO4Na), sodium lauryl sulfate (C12SO4Na), and sodium tetradecyl sulfate (C14SO4Na) has been studied by conductivity, spectrophotometry and surface tension measurements. The surface properties of anionic surfactants, that is, maximum surface excess concentration ((max)) and minimum area per surfactant molecule (A(min)) at the air/water interface have been evaluated in the absence and presence of TMP using Gibbs adsorption isotherm. From conductivity data the ionization degree and counterion binding parameter have been obtained. Spectrophotometric experiments were used to determine binding constants of TMP to anionic micelles. With the increasing alkyl chain of surfactants, the interaction becomes stronger, which shows the importance of hydrophobic forces and incorporation of TMP molecules to the pure micelles of anionic surfactants increased. The results obtained from the surface tension and conductometric studies have been correlated with those obtained from the spectroscopic studies and binding tendency of TMP to anionic micelles followed the order as: C14SO4Na>C12SO4Na>C10SO4Na>C8SO4Na. From these results, the study of the interaction TMP in different anionic micellar solutions provided information about the characteristics of binding properties of poorly soluble drugs.
Keywords: Binding constant; counterion binding parameter; drug-surfactant interaction; surface tension; trimethoprim; SOLUBILIZATION; SURFACTANT; BEHAVIOR; DYES; HCL